Social Innovation Model In Indigenous Community - Timothy Andrianus Philemon; Maria Widyarini; Tutik Rachmawati; Elivas Simatupang (Jurnal Administrasi Bisnis, 2022)
During the past decade, social entrepreneurship has become an emerging topic. The primary objective of social entrepreneurship is to address social issues through a business lens. Social capital is a critical indicator of a social enterprise's sustainability. The purpose of this conceptual paper is to examine social capital and its role in the innovation process. At the moment, no valid model adequately describes the role of social capital in social innovation, particularly in indigenous communities. The available model is intended for use in the private sector only for social innovation. The purpose of this paper is to discuss bridging and bonding at the level of actor-actor interaction to the innovation process in the Cireundeu indigenous community. Social innovation is believed to stimulate business growth by leveraging additional ideas from external sources, providing a new capacity for the community to develop a local economy. This paper aims to develop a conceptual model of social capital in social innovation to understand the actors' innovation capabilities better.